Analysis of the Impact of Perceived Usefulness and Perceived Ease of Use on Intention to Use Digital Technology in the African Oil and Gas Industry - Nwokolu, Greg Svenson (Journal of Current Research In Multidisciplinary, 2025)
Digital transformation has become a crucial factor for the sustainability of the global oil and gas industry; however, its adoption in the African region still faces various structural and competency challenges. This study aims to analyze the influence of Digital Literacy and Organizational Support on the Intention to Use Digital Technology among the workforce in the African oil and gas industry. Using a quantitative approach, data were collected through a survey of 250 professionals in the oil and gas sector across key countries such as Nigeria, Angola, and Egypt. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that both Digital Literacy and Organizational Support have a positive and significant influence on the intention to use digital technology. Digital literacy is proven to lower psychological and technical barriers to accepting innovation, while organizational support in the form of infrastructure provision and adaptive management policies acts as a catalyst that strengthens employee confidence. These findings confirm that to achieve successful digital transformation in Africa, companies must not only invest in hardware but also prioritize human capital development and create a work ecosystem that fosters innovation. This research provides managerial implications for energy industry leaders in Africa to formulate holistic digitalization strategies to enhance operational efficiency and global competitiveness.